Structural and Optical Properties of Cadmium Sulfide-doped Silver Deposited on Glass and Polymer Substrates by Chemical Spray Pyrolysis - Hamad, Niaz H.; Faraj, Mohammad G.; Taha, Akram H. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2023)
This process of this paper is carried out using thechemical spraying method to produce homogeneous thin films ofpure cadmium sulfide-doped with silver at different percentagesof 1%, 3%, and 5% on glass and polyimide plastic substrates at300°C. The aim is to study the optical and structural properties of the samples and the effect of the silver doping rate on films producedwith these properties. Due to X-ray diffraction studies, all filmscreated had a hexagonal phase, and it was noticed that they had avery precise structure free of holes or cracks. The obtained crystalsize ranged between 22.74 nm and 55.05 nm for different substrates, and the prominent plane was (002). From the optical properties, all films exhibited transmission higher than 60%, thus showing a lowabsorption, which makes them be used as light-permeable layers in the Solar Cell system. In addition, emission peaks were revealed by photo luminescence spectra examination at wavelengths ranging between (542.94 nm) and (546.02 nm), which led to calculate the energy gap (Eg). of the produced films, ranged between (2.27 eV) and (2.28 eV) for the different substrates.